STRATEGI PENANGANAN KASUS KEKERASAN TERHADAP ANAK DI KABUPATEN TEGAL TAHUN 2020 - Zahroo, Fathimah -; Herawati, Nunik Retno (Journal of Politic and Government Studies, 2022)
The case of violence against children today has become a frightening specter among the community considering this issue is an iceberg phenomenon whose case level has not decreased significantly. In this study, the author discusses the strategy for handling cases of violence against children by conducting a research study at the Office of Women's Empowerment, Child Protection, Population Control and Family Planning (P3AP2 and KB Offices) in Tegal Regency. The purpose of this study is to analyze the extent of strategic management carried out by the P3AP2 and KB Offices of Tegal Regency in handling cases of violence against children by looking at the phenomenon of cases of violence that occurred in 2020. This study uses a qualitative research method with a descriptive approach. By using this method, researchers can obtain data that is credible and in accordance with social realities related to this research. The data obtained in this study were obtained through the process of interviewing sources, observation, and case studies. The analysis and interpretation of the data carried out in this study consisted of data reduction, data presentation, and drawing conclusions. The results of this study indicate that the Tegal Regency P3AP2 and KB Offices are guided by the 2019-2024 Regency RPJMD and Tegal Regency Regional Regulation No. 5 of 2016 in the preparation of strategic plans. Empirical facts in 2020 show that cases of violence against children such as physical, psychological, sexual, and social violence are still a serious problem with a total of 33 cases where cases of sexual violence still occupy the highest number. With the help of the PPT Team and cross-OPD partnerships, the P3AP2 and KB Services carried out various programs including welfare & fulfillment of children's rights as well as protection & improvement of children's quality of life which later succeeded in handling all cases of child violence reported in 2020. However, the agency has not succeeded. in increasing public awareness to report cases of child abuse, it is proven by the stagnant number of reported cases. This is due to the ineffectiveness of the agency in taking preventive steps to the grassroots level and the inactive role of NGOs that focus on child protection in Tegal Regency. This study recommends that the P3AP2 and KB Offices of Tegal Regency strive to maximize the process of preparing, implementing, and evaluating performance in a rooted manner and maximizing preventive measures to the grassroots level. In addition, it is necessary to increase interconnection between fields, implement digital-based programs, and strengthen partnerships with cross-sectoral / OPD and NGOs so that they are able to produce an integrated, fast, and precise movement in handling cases of violence against children in Tegal Regency